Percepción y actitudes de internos de enfermería en la calidad de atención de pacientes con vih/sida. - Martinez Delgado, Javier Alexander (My University, 2024)
Perception is the interpretation of information about the degree to which services provide health care, through the altruistic, competitive or aggressive attitude demonstrated by inmates towards patients with HIV / AIDS. In 2023 there were 4 million people with HIV in the Americas, 2.7 million lived in Latin America and the Caribbean, people dying from AIDS has decreased from 42 thousand in 2010 to 30 thousand in 2023. The perception and attitudes that Nursing interns have towards patients with HIV / AIDS influences the quality of the service provided, such as: knowledge of HIV / AIDS, personal beliefs, stigma associated with HIV, previous experiences in the hospital field. Objective: To describe the perception and attitudes of nursing interns in the care of patients with HIV / AIDS at the General Hospital 'Teófilo Dávila. Methodology: quantitative research, descriptive study. Study design: observational, non-experimental cross-sectional. The sample consisted of 80 nursing inmates at Machala Hospital. Results: Perceptions of care for patients with HIV were associated with stigma and discrimination, while attitudes toward patients with HIV/AIDS were positive, and the quality of care they perceived was adequate. Conclusion: Nursing Interns' perceptions are important. Labeling patients will be prevented, and attitudes will be demonstrated through their relationship with the perceived quality of health care, especially among people living with HIV.
Percepción es la interpretación de la información sobre el grado que los servicios brindan atención de salud, a través de la postura altruista, competitiva o agresiva que demuestran los internos frente a pacientes con Vih/Sida. En 2023 había 4 millones de personas con VIH en las Américas, 2,7 millones vivían en América Latina y el Caribe, las personas que mueren por SIDA ha disminuido de 42 mil en 2010 a 30 mil en 2023. La percepción y las actitudes que poseen los internos de Enfermería hacia los pacientes con VIH/SIDA, influye en la calidad del servicio brindado, como son: conocimiento del VIH/SIDA, creencias personales, estigma asociado al VIH, experiencias previas en el campo hospitalario. Objetivo: Describir la percepción y actitudes de los internos de enfermería en la atención de pacientes con VIH/SIDA en el Hospital General 'Teófilo Dávila. Metodología: investigación cuantitativa, estudio descriptivo. Diseño del estudio: observacional de corte transversal no experimental. La población son 80 internos de enfermería del Hospital de Machala. Resultados: la percepción sobre la atención a pacientes con VIH se relaciona con el Estigma y discriminación, mientras que la Actitud ante Pacientes con VIH/SIDA es Positiva, y la Calidad de Atención que perciben es Adecuada. Conclusión: la percepción que tengan los Internos de Enfermería, es importante, se prevendra la etiqueta a los pacientes, la actitud se demuestre por su relación con la calidad sentida en la atención de salud, más aun siendo personas con VIH.
Keywords: ATENCION EN SALUD; VIH/SIDA; ENFERMERIA; PERCEPCION